Bio Informatika Drone - Fitrah Hsb, Dafa Rizki Rahmanda; Rangkuti, Emir Khalil; Siregar, Fathur Rahman; Zailani, Zaqi Hudzaifah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The rapid advancement of drone technology presents significant potential in various fields, including bioinformatics. This article explores the integration of drone technology in bioinformatics, focusing on environmental monitoring and biological data collection. By enabling efficient sampling and access to hard-to-reach areas, drones enhance the quality and quantity of collected biological data. This integration facilitates comprehensive data analysis, supporting research in ecology, conservation, and biodiversity studies.